Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank Group (World Bank, Washington, DC, 2021)
The Palestinian economy has started its recovery in 2021 as COVID-related (coronavirus) measures have been eased, but sustainable sources of growth going forward remain limited. Given the decline in the daily number of new COVID-19 cases, lockdowns have been significantly eased in 2021. This combined with the pickup of the vaccination campaign allowed consumer confidence to slowly pick up and business activity to gradually rebound. The economy is estimated to have grown by 5.4 percent, in real terms, in the first half (H1) of 2021, year-on-year. The improved economic performance was fully driven by the West Bank economy while Gaza’s economy remained almost stagnant in H1 2021 due to the 11-day conflict in May. Growth is expected to further pick up throughout the remainder of the year and reach 6 percent in 2021 as the West Bank economy continues to regain more of what was lost during 2020 and with the implementation of some Israeli confidence building measures supporting economic activity and facilitating reconstruction in Gaza. In the following years, growth is expected to hover around 3 percent as the low base effect weakens and as sources of growth remain limited given the ongoing restrictions on movement, access and trade. Unemployment remained stubbornly high in 2021, mainly driven by Gaza. The unemployment rate in the Palestinian territories reached 26.4 percent in the second quarter of 2021: 16.9 percent in the West Bank and 44.7 percent in Gaza, reflecting the particularly difficult economic situation in the Strip due to the effect of the 11-day conflict and the ongoing restrictions. The extremely high unemployment rate in Gaza comes hand-in-hand with deteriorating social conditions in the Strip. Estimates by the World Bank indicate that the recent conflict has pushed poverty in Gaza to 59.3 percent in 2021 (using 5.50 US Dollars a day (2011 PPP) international poverty line). This is 2.3 percentage points higher than the COVID-19 induced peak in 2020, and a 16.3 percentage point increase above the 2016-2017 values (latest available official data).